Seeing a Work of Art Indirectly: When a Reproduction Is Better Than an Indirect View, and a Mirror Better Than a Live Monitor - Bertamini, Marco; Blakemore, Colin (Frontiers in Psychology, 2019)
Visiting a museum and seeing an original artwork can be a special experience. We use a survey and a set of hypothetical questions to explore how such experience would be affected by changes in how the artwork is seen. In a first study, participants imagined that they had travelled to see a painting that they particularly like. They discover that it is impossible to directly see the original painting. Three alternatives are offered: seeing an optical reflection (using a mirror), seeing a video screening (a closed-circuit camera) or seeing a reproduction. In all cases it is made clear that the size, brightness, and resolution will match that of the original. In addition, these options could be within the same room as the original, in the room next door, or in a different building. Results show that physical distance did not affect significantly the responses. However, there was an overall preference for seeing a reproduction as opposed to an optical or digital image. Contrary to the idea that the original is always superior to a copy, many people felt that a direct view of a copy is a preferable experience than an indirect view. The second study was focused directly on the comparison between a mirror and a monitor. Here we highlighted the fact that for the mirror light coming from the mirror originated from the painting. Data were collected in Britain and in China. In both cases there was a clear preference for the mirror over the monitor.